Osteoporosis treatment in Portugal: trends and geographical variation. - Rocha, Olavo (2007)
The drugs available in the Portuguese market, for the treatment of osteoporosis, have different mechanisms of action, efficacy, indications, safety profile, and cost, which may influence prescription and acquisition by patients.To describe the use of drugs for osteoporosis treatment (estimated by sales), between 1998 and 2004, and the geographical variation in the drug utilization, in 2004.Data was obtained from IMS Health for the sales of drugs used in the ambulatory treatment of osteoporosis, in the whole country, from 1998 to 2004, and by region, in 2004. For each group (bisphosphonates, raloxifene, calcitonins, Hormone replacement therapy (HRT) and calcium and vitamin D), we computed the sum of the amount of packages and the value of the sales in each year, regardless of the strength or the package size. For bisphosphonates, raloxifene and calcitonins, we computed the DDD (Defined Daily Dose) sold in Portugal. All consumption data are presented by women aged 45 to 74 years. National data was used to describe the trends in sales, from 1998 to 2004, and regional data was used to map the 2004 consumptions.The expenses with drugs used in osteoporosis increased 60% from 1998 to 2004. The bisphosphonates sales increased more than five times, and in 2004 this group was responsible for 60% of the national market of drugs for osteoporosis treatment. Raloxifene represented approximately 10% of the sales in 2004. The consumption of calcitonins decreased nearly 70% in the observation period. The use of HRT increased 30% to 40% until 2001/2002, and decreased just about the same from there on. Geographical differences were observed in the sales of osteoporosis drugs in 2004, the amplitude of variation ranging from two (bisphosphonates, calcium and vitamin D, HRT) to three times (raloxifene, calcitonins) across regions. The lowest consumptions were observed in Beja and Bragança, and the highest in Aveiro. Raloxifene is used mainly in the Northwest of the country, and HRT in the sea side regions.In Portugal, the trends in the consumption of drugs used for osteoporosis treatment, as well as the relative weight of each pharmacological group, follow a similar pattern to the observed in other countries. The differences in consumption across the years and regions may reflect a variation in the frequency of disease or in the proportion of subjects being treated, but the magnitude of the variation suggests that there are unmet needs in diagnosis and treatment of osteoporosis in our country, and that social and economic factors may contribute to the regional differences observed.